Correlation of Rice Production and Greenhouse Gas Emissions in North Sulawesi Province - Andreas Aprilano Thomas Suli; Mario Damanik (Jurnal Ilmu Pertanian Indonesia, 2023)
This study aimed to reveal correlation, calculate significance, and discover the regression equation of rice production to Green House Gas (GHG) emission in North Sulawesi Province. The data on GHG emissions from rice cultivation (Gg CO2eq) was obtained from the Ministry of Environment and Forestry of Indonesia. Data on rice production from wetland and dryland (Gg) was from the BP Statistical Review annual period of 2000-2021, both for North Sulawesi Province. Data analysis of correlation coefficient, F-test for Regression, and Simple Regression Analysis will be processed with the help application of MS Excel. The results show that the correlation between rice production and emission of rice cultivation in North Sulawesi Province is 0.53 and classified as a moderate correlation. The coefficient of determination stated that the emission of rice cultivation could be explained by about 28.6% from rice production. Therefore, rice production is statistically significant to the emission of rice cultivation with a 5% confidence level for North Sulawesi Province. Furthermore, this study found a regression equation, emission of rice cultivation is 112.67 + 0.516 times rice production. Keywords: correlation coefficient, green house gas emission, rice production